The Effectiveness of Video-Based Diabetic Foot Wound Care Education in Post Hospitalization Patients as an Effort to Increase Patient Knowledge: Systematic Review - Juni Netti Mardian; Masfuri -; Riri Maria (Jurnal Ipteks Terapan, 2023)
Introduction : Wound is a damage to the integrity of the skin that can occur when the skin is exposed to temperature or pH, chemicals, friction, pressure trauma and radiation. Video learning is a learning method that uses recorded videos to assist in the learning process. Using this method, it can provide a stimulus to three important parts of learning, namely emotional, intellectual and physicomotoric. Methods: A systematic review approach is used to systematically evaluate the results of studies that assess the effectiveness of using the video method in providing education on diabetic foot care. Conclusion: From the results of a review of the five articles, it can be concluded that the educational video method can significantly increase patient knowledge in treating diabetic foot wounds